Adipose-Derived Mesenchymal Stem Cells Modulate Fibrosis and Inflammation in the Peritoneal Fibrosis Model Developed in Uremic Rats - Elerson C. Costalonga; Camilla Fanelli; Margoth R. Garnica; Irene L. Noronha (Stem Cells International)
Peritoneal fibrosis (PF) represents a long-term complication of peritoneal dialysis (PD), affecting the peritoneal membrane (PM) function. Adipose tissue-derived mesenchymal stem cells (ASC) display immunomodulatory effects and may represent a strategy to block PF. The aim of this study was to analyze the effect of ASC in an experimental PF model developed in uremic rats. To mimic the clinical situation of patients on long-term PD, a combo model, characterized by the combination of PF and chronic kidney disease (CKD), was developed in Wistar rats. Rats were fed with a 0.75% adenine-containing diet, for 30 days, to induce CKD with uremia. PF was induced with intraperitoneal injections of chlorhexidine gluconate (CG) from day 15 to 30. 1×106 ASC were intravenously injected at days 15 and 21. Rats were divided into 5 groups: control, normal rats; CKD, rats receiving adenine diet; PF, rats receiving CG; CKD+PF, CKD rats with PF; CKD+PF+ASC, uremic rats with PF treated with ASC. PF was assessed by Masson trichrome staining. Inflammation- and fibrosis-associated factors were assessed by immunohistochemistry, multiplex analysis, and qPCR. When compared with the control and CKD groups, GC administration induced a striking increase in PM thickness and inflammation in the PF and CKD+PF groups. The development of PF was blocked by ASC treatment. Further, the upregulation of profibrotic factors (TGF-β, fibronectin, and collagen) and the increased myofibroblast expression observed in the CKD+PF group were significantly ameliorated by ASC. Beyond the antifibrotic effect, ASC showed an anti-inflammatory effect avoiding leucocyte infiltration and the overexpression of inflammatory cytokines (IL-1β, TNF-α, and IL-6) in the PM induced by GC. ASC were effective in preventing the development of PF in the experimental model of CKD+PF, probably due to their immunomodulatory properties. These results suggest that ASC may represent a potential strategy for treating long-term PD-associated fibrosis.